2016
DOI: 10.3892/ijo.2016.3492
|View full text |Cite
|
Sign up to set email alerts
|

αβ T-cell receptor bias in disease and therapy (Review)

Abstract: Abstract.The diversity and specificity of T cell receptors (TCR), the characteristics of T-cell surface marker, are central to the adaptive immunity. TCR variability is required for successful immunization coverage because this structural foundation is indispensable for the valid identification of short antigen peptides (derived from degraded antigens) that are presented by major histocompatibility molecules on the surfaces of antigen-presenting cells. Despite the vast T-cell repertoire, biased αβ TCR has beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 93 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…Recently, biased αβTCR repertoires and TCR “signatures” raised against specific antigens have been observed in various diseases, especially in virus infections, autoimmune disorders, and tumor (10). Little is known about whether, and if so how MHC genotype influences the composition of TCR repertoire.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biased αβTCR repertoires and TCR “signatures” raised against specific antigens have been observed in various diseases, especially in virus infections, autoimmune disorders, and tumor (10). Little is known about whether, and if so how MHC genotype influences the composition of TCR repertoire.…”
Section: Introductionmentioning
confidence: 99%
“…34 Furthermore, infections and tumors can drive an antigen-mediated bias in ab TCR repertoires. 88 Although only a few studies have monitored TCR repertoires in patients or mice treated with rAAV vectors, the robust T-cell response against an AAV transgene in one trial was shown to be associated with a biased TCRBV repertoire. 89 Therefore it was important to assess the repertoire diversity in our gene-corrected mice.…”
Section: Intrathymic Aav8-zap-70 Transduction Promotes Long-term Mainmentioning
confidence: 99%
“…Based on this assumption, we attempted to identify CSFV-specific TCRs using the GeneScan spectratyping method. The degree of clonal proliferation and the functional status of T cells can be detected by monitoring the spectratypes, length or sequence of the CDR3 region of the TCR 27 . To the best of our knowledge, the present study is the first to describe the diversity and clonality of αβTCRs in CD4 + T cells from miniature pigs immunised with C-strain vaccine by immunoscope spectratyping.…”
Section: Discussionmentioning
confidence: 99%
“…In human’s TCR research, M. tuberculosis 38-kDa antigen-specific TCRs were screened and expressed in TCR-gene modified CD4 + and CD8 + T cells, antigen-specific secretion of cytokine and cytolytic activity were seen in TCR gene modified CD4 + and CD8 + T cells 33 . In addition, antigen-associated monoclonal TCR Vα and Vβ gene families can be incorporated into antitumor or antiviral disease therapy 27 , 34 . Two patients with CD8 + T cells which were genetically engineered to express the melanoma MART-1-restricted TCRα/β gene win 18 months life time without this disease 35 .…”
Section: Discussionmentioning
confidence: 99%